Blockchain-Based ERP System: Architecture and Opportunities for Future - Morteza Moalagh; Amin Ebrahimi Ghadi (Journal of Information Technology Management)
Although Blockchain can significantly change the future of ERP systems as an innovative tech-nology, few researchers have gone into the details of this development. Most have given an overview of the changes ahead. Therefore, in this research, we have tried to use the method of Exploratory Content Analysis (ECA) by reviewing more than three hundred scientific articles in the field of Blockchain to analyze the effects of this technology on ERP system modules such as supply chain management, maintenance, finance, project management, manufacturing, and hu-man capital management. The result of this exploratory research is an architectural model for a blockchain-based ERP system. The researchers describe the functions of this system carefully, and the role of supporting technologies such as Smart Contract, IoT, Digital Wallet, Cloud Com-puting, and Building Information Model is clarified. We genuinely believe that this research could use as a reference model for ERP vendors and researchers in information systems and business process management